AGRONOMIC BEHAVIOR OF Oryza sativa L. (RICE) AND Manihot esculenta Crantz (YUCA) IN TWO SEEDING LOCATIONS IN LORETO, PERU - CUMARI LAULATE, Elías (2020)
In Loreto region, many efforts have been made to obtain high yields of cassava and rice, which have moderate yield potentials; these crops are a guarantee of food for the population, since they are in great demand by the rural population of the Amazon. The objective of the study was to determine the behavior of Oryza sativa L. variety "INIA 509 la esperanza" and Manihot esculenta crantz variety "señorita" in two localities of sowing in Loreto region. They were sowed under a system of Bactris gasipaes H.B.K "pijuayo" in the localities El Dorado and Bolloquito located in the axis of the highway Iquitos-Nauta in the Peruvian Amazon. The rice cultivation showed statistical significance (p<0.01) in the agronomic characteristics with higher averages in El Dorado for plant height (81.61 cm), quantity of bushes (21.55), quantity of panojas (21.55), weight of grains per bush (0.08 kg) and grain yield (2656.14 k/ha). In cassava cultivation they showed statistical significance (p< 0,01) in the agronomic characteristics with higher averages in Bolloquito as plant height (255.55 cm) and first branch height (130.22 cm), while in El Dorado they showed statistical significance (p< 0.05) for root weight per plant (2.59 kg) and root yield (19689.07 kg/ha), the crops behave according to the sowing localities, expressing better agronomic characteristics and yields in a specific way.